The effects of synthetic and natural scaffolds on viability and proliferation of adipose-derived stem cells. Issue 1 (2nd January 2016) - Ghiasi, Mahdieh; Kalhor, Naser; Tabatabaei Qomi, Reza; Sheykhhasan, Mohsen
ABSTRACT: This study presents a comparative assessment of adipose-derived stem cell (ADSCs) proliferation rates and their viability on five different scaffolds. Five different biomaterial scaffolds were prepared: alginate, poly lactic-co-glycolic acid, fibrin glue, inactive platelet-rich plasma, and active platelet-rich plasma (APRP). Stem cells were isolated from human adipose tissue. Flow cytometry analysis was performed. Specifically, adipogenesis/osteogenesis/chondrogenesis-associated genes expression was analyzed by real-time polymerase chain reaction. These cells were seeded in the prepared scaffolds. After 14 days, the proliferation and viability of MSCs were evaluated using an MTT assay. Also, stemness genes expression was analyzed with the reverse transcriptasepolymerase chain reaction (RT-PCR) method. In addition, the DNA content assay was also performed. The obtained results showed a significant difference between cell proliferation and viability of different scaffolds. APRP and alginate were shown to be the most and least suitable scaffolds in terms of enhancing cell proliferation and maintaining cell viability respectively ( p < .05). RT-PCR reactions demonstrated the expression of the various stemness-related markers (Nanog, Octamer4A, and Sox2) when ADSC cells were grown separately on the five different scaffolds. Our study indicates that compared with the scaffolds, APRP could be the best scaffold for support of ADSC proliferation.